Hand Gesture Animation Model for Local Hand Motion - Hazarika, Bidit; Das, Dipankar; Changkakoti, Dibyajyoti; Deka, Abhinov; Pradhan, Adarsh (International Journal of Computer Sciences and Engineering, 2025)
This paper aims to introduce a technique concept for facilitating communication between deaf & dumb and normal people. We propose a system which helps in translating speech/text into equivalent hand gestures. This can be done by image processing and/or animation techniques. With this application we hope to reduce the communication gap between ‗deaf & dumb‘ and normal people by eliminating the need of a human translator